2020
DOI: 10.1093/molbev/msaa328
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Robust Identity-by-Descent Inference with the Templated Positional Burrows–Wheeler Transform

Abstract: Estimating the genomic location and length of identical-by-descent (IBD) segments among individuals is a crucial step in many genetic analyses. However, the exponential growth in the size of biobank and direct-to-consumer genetic data sets makes accurate IBD inference a significant computational challenge. Here we present the templated positional Burrows–Wheeler transform (TPBWT) to make fast IBD estimates robust to genotype and phasing errors. Using haplotype data simulated over pedigrees with realistic genot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…The RaPID [ 18 ] software package and source code are available at RaPID’s GitHub [ 42 ]. The TPBWT [ 22 ] software package and source code are available at TPBWT’s GitHub [ 43 ].…”
Section: Data Availabilitymentioning
confidence: 99%
“…The RaPID [ 18 ] software package and source code are available at RaPID’s GitHub [ 42 ]. The TPBWT [ 22 ] software package and source code are available at TPBWT’s GitHub [ 43 ].…”
Section: Data Availabilitymentioning
confidence: 99%
“…have demonstrated that half-sibling, avuncular, and grandparental relationships, which have been difficult to differentiate historically due to the fact that the total amount of IBD is the same for each of these relationship types, can be differentiated by making use of long-range phasing information. Phased IBD estimates, obtained from programs such as the PhasedIBD method of Freyman et al (2020), could provide a considerable boost in accuracy for close relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hap-IBD may run the PBWT in parallel, thus showing the best performance among algorithms benchmarked in UK BioBank data. Similarly, investigators at 23andMe leveraged the same PBWT to develop their new Templated PBWT framework (Freyman et al, 2021) with similar properties and efficient, scalable runtime. TPBWT is notable for attempting to identify and correct phase switch errors, thereby improving IBD tract length estimation and longrange phasing.…”
Section: Overview Of Methodsmentioning
confidence: 99%